Representation Social Concern in the Novel Orang Miskin Dilarang Sekolah: Strengthening the Profile of Pancasila Students in Schools - Indiyah Purwaningsih; Widayati, Mukti; Nurnaningsih, Nurnaningsih (Universitas Cokroaminoto Palopo, 2025)
The purpose of this study is to describe the representation of social concern and how it reinforces the Pancasila Student Profile through the literary narrative of the novel Orang Miskin Dilarang Sekolah by Wiwid Prasetyo. This qualitative research employs a descriptive content analysis method with a literary sociology approach. Data were collected using listening, reading, and note-taking techniques on textual elements—words, phrases, sentences, and quotations—that contain elements of social concern. Data were obtained from the primary source (the novel) and supported by secondary textual references. Sampling was conducted purposively, and data validity was ensured through triangulation of sources and theories, as well as peer review and observer persistence. The data were analyzed through content analysis followed by dialectical techniques to identify interactions between social values and character formation. The findings reveal four main representations of social concern: (1) inequality in access to education, (2) societal indifference toward the poor, (3) individual resistance to social injustice, and (4) family empathy towards children's educational aspirations. These elements significantly contribute to the internalization of Pancasila Student Profile values, including mutual cooperation, independence, social justice, and empathy. The novel thus functions not only as a reflection of social reality but also as a medium to strengthen the values of character education aligned with national ideology.